Innovative Green-Technology SMEs as an Opportunity to Promote Financial De-Risking (International Journal of Innovative Research in Engineering & Management, 2021)
The authors propose that the G20  concentrate on sustainable construction SMEs as a method  to boost financial de-risking while satisfying the Paris  Agreement's promises and the United Nations Sustainable  Development Goals. And according to G20/OECD Higher  Levels of motivation of SMEs Financing, SMEs,  comprising small - angle x, are vital engines of  entrepreneurship, investment, business growth, and  empowerment in viable options as well as moderate  emerging nations. This should be actually achieved by  timely manner for international investment through: (1) an  investigating structure that enables monitor the scale-up of  green-technology SMEs; (2) the use of taxpayer resources  to signal application of green SMEs to investment firms;  and (3) the involvement of SMEs inside this prototype of  carbon trading platforms. The G20 will ensure that  modern, low-carbon SMEs becomes appealing, low-risk  economic opportunities for the corporate companies by  adopting these suggestions.
Keywords: De-Risking; Finance; Green Technology; SME.